Characterization and Nutritional Intervention Effects of Canna edulis Type 5 Resistant Starch in Hyperlipidemia Mice - Houxier Li; Nan Wang; Jiahui Wu; Shuting Tan; Yan Li; Nan Zhang; Li Yang; Aji Li; Rongting Min; Maochun Xiao; Shiyao Su; Xiang Wang; et al. (Foods)
Numerous reports have indicated that the type 3 resistant starch (RS3) derived from Canna edulis can regulate lipid metabolism. However, it remains unclear whether the type 5 resistant starch (RS5) exhibits similar effects. In this study, RS5 was prepared from Canna edulis native starch and lauric acid through a hydrothermal method for the first time, and its nutritional intervention effects on hyperlipidemia in mice were investigated. The Canna edulis type 5 resistant starch (Ce-RS5) prepared using Canna edulis native starch and lauric acid exhibited a high compound index and resistant starch content, along with decreased swelling power and enhanced starch granule stability. The crystallinity of Ce-RS5 was decreased, and its crystal structure displayed a B+V pattern. Microscopically, the surface appeared rough with deepened grooves, and the granules were loose. Feeding mice with 1.5 g/kg and 3 g/kg of Ce-RS5 significantly reduced their body weight, positively regulated their blood lipid levels, and improved liver damage and fat accumulation. Additionally, Ce-RS5 promoted the abundance of beneficial gut bacteria, such as norank_f_Muribaculaceae, and inhibited the abundance of harmful bacteria like Colidextribacter. This study provides the first evidence of the hypolipidemic and weight loss effects of Ce-RS5 in hyperlipidemia mice.